Mid-Triassic felsic igneous rocks from the southern Lancangjiang Zone, SW China: Petrogenesis and implications for the evolution of Paleo-Tethys - Peng, T.; Wilde, Simon; Wang, Y.; Fan, W.; Peng, B. (Elsevier BV, 2013)
The southern Lancangjiang magmatic belt is an important component of the Triassic San-Jiang igneous zone in Southwestern China and is mainly composed of the Lincang (LC) batholith and aMesozoic volcanic belt that contains abundant rhyolites. Our new LA-ICP-MS zircon U–Pb results, together with previous SHRIMP and LA-ICP-MS ages, define two emplacement ages for the Lincang batholith: at ~230 Ma and ~220 Ma, corresponding to the eruption times of volcanic rocks of theManghuai and Xiaodingxi formations, respectively.Most of the ~230 Ma LC granites possess high A/CNK values (>1.1) and display strongly peraluminous characteristics, similar to S-type granite, whereas the Manghuai Formation (MHF) rhyolites show an affinity to A-type granite, especially their elevated FeOt/(FeOt+MgO) and Ga/Al ratios. Both of the granitic and volcanic rocks have strongly fractionated REE patterns ((La/Yb)N=2.66–33.2 and 13.1–19.7, respectively) and have conspicuous negative Eu anomalies (Eu*/Eu=0.06–0.65 and 0.52–0.74, respectively) with a similar depletion in HFSE (Nb,Zr, Hf), P, Ba and Sr. The Sr–Nd isotopic data and TDM2 model ages suggest that the LC graniticmagma had a dominantly crustal source,whereas theMHF rhyoliteswere derived frommixing betweenmiddle/upper crustal rocks similar to the source of the LC granitic magma, with a small volume of mantle-derived melt.In combination with regional studies, our new geochemical data and geochronological results show that the mid-Triassic magmatism was generated in a post-collisional tectonic setting. The spatial distribution pattern of the Mesozoic igneous rocks along the Lancangjiang zone favors a slab breakoff model, which resulted in post-collisional extension and asthenospheric upwelling that induced large-scale partial melting of the middle-lower crust to produce voluminous amounts of felsic magma. Therefore, the occurrence of the mid-Triassic post-collisional magmatism clearly indicates that the final continent–continent/arc collision between the Gondwana-derived Sibumasu and Indochina blocks of Paleo-Tethys was completed by the early mid-Triassic.